SINERGI PEMBELAJARAN DIGITAL DAN KONVENSIONAL: TRANSFORMASI PENDIDIKAN MATEMATIKA DI SMPN 25 MALANG - Randi RAndi; Mila Intan Lestari; Elita Mega Selvia Wijaya; Nila Kartika Sari (Inteligensi : Jurnal Ilmu Pendidikan, 2024)
The year 2024 marks a pivotal moment for digital transformation within public schools. This study aims to analyze the synergy between digital and conventional learning in mathematics education at SMP Negeri 25 Malang. Using a descriptive qualitative approach, this research captures how students integrate digital tools with traditional learning methods in the classroom. The results indicate that functional integration between dynamic mathematics applications and textbook literacy creates an adaptive learning ecosystem. Key findings reveal improvements in student motivation and numeracy assessment outcomes. Furthermore, this study highlights the crucial role of teachers as facilitators in bridging technology use to remain aligned with the development of critical thinking logic. This synergy is consistent with modern learning theories that emphasize material contextualization, as developed in current mathematics education literature. In conclusion, the transformation at SMPN 25 Malang provides a model for other schools in managing an inclusive and sustainable digital transition.